Colour pattern does not play a key role in forming a mimetic complex of red-and-black insects. Experiments with na\"\i{}ve and adult great tits - Drábková, Tereza (Jihočeská univerzita, 2016)
Reactions of wild-caught adult and naive great tits (Parus major) to colour patterns of seven chosen aposematic insect prey species were studied in laboratory tests. Conspicuous patterns were transferred to palatable prey using paper stickers to test their effects on the reactions of predators and to determine the importance of a colour pattern in the formation of a mimetic complex.
Colour pattern does not play a key role in forming a mimetic complex of red-and-black insects. Experiments with na\"\i{}ve and adult great tits